Analysis of the intervening characteristics of the environment of nurses' practice in the hospital space (Research, Society and Development, 2022)
Objective: To analyze the association between the practice environment and sociodemographic and professional characteristics among nurses. Method: study with a cross-sectional, analytical design, quantitative approach, in a public hospital. The population consisted of professional nurses. To investigate the intervening characteristics in the practice environment, we used the Practice Environment Scale instrument adapted and validated for the Brazilian culture. Results: 103 (88.04%) professional nurses participated in the study. The data revealed that 62.14% of the professional nurses perceived their professional practice environment as unfavorable. Correlation was identified with the variables: marital status, nature of the bond, nature of the function, staffing unit and working time in the institution. Conclusions: Increasing evidence on the reflection of unfavorable environments for professional nursing practice will result in an improvement in the quality of work while providing conditions for managers to plan and implement programs aimed at working environments that are favorable to professional practice.